Mycovirus Fusarium oxysporum f. sp. dianthi Virus 1 Decreases the Colonizing Efficiency of Its Fungal Host - Torres-Trenas, Almudena; Prieto, Pilar; Cañizares, M. Carmen; García-Pedrajas, María Dolores; Pérez-Artés, Encarnación (Frontiers in Cellular and Infection Microbiology, 2019)
Mycoviruses that induce hypovirulence in phytopathogenic fungi are interesting because their potential use as biological control agents of the plant diseases caused by their fungal hosts. The recently identified chrysovirus Fusarium oxysporum f. sp. dianthi virus 1 (FodV1) has been associated to the induction of hypovirulence in Fusarium oxysporum f. sp. dianthi (Fod), the forma specialis of F. oxysporum that causes vascular wilt in carnation (Dianthus caryophyllus). In this work, we have used confocal laser scanner microscopy and two isogenic GFP-labelled strains of Fod infected (V+) and not infected (V-) with the Fusarium oxysporum f. sp. dianthi virus 1, respectively, to analyse the effect of mycovirus FodV1 on the plant colonization pattern of its fungal host. Results demonstrate that FodV1-viral infection affects the speed and spatial distribution of fungal colonization into the plant. Initial stages of external root colonization were similar for both Fod strains, but the virus-free strain colonized the internal plant tissues faster than the virus-infected strain. In addition, other differences related to the specific zone colonized and the density of colonization were observed between both Fod strains. The hyphae of both V- and V+ strains progressed up through the xylem vessels but differences in the number of vessels colonized and of hyphae inside them were found. Moreover, as colonization progressed, V- and V+ hyphae propagated horizontally reaching the central medulla but, while the virus-free strain V- densely colonized the interior of the medulla cells, the virus-infected strain V+ appeared mainly in the intercellular spaces and with a much lower density of colonization. Finally, the incidence of FodV1-viral infections in a collection of 221 isolates sampled between 2008 and 2012 in the same geographic area where the originally infected isolate was obtained has been also analyzed. The very low (2%) incidence of viral infections is discussed here. To the best of our knowledge, this work provides the first microscopic evidence about the effect of a hypovirulence-inducing mycovirus on the pattern of plant colonization by its fungal host.